Strategi Social Media Marketing di Masa Pandemi Covid-19 Terhadap Peningkatan Business Value UMKM - Holmes Rolandy Kapuy; Gusstiawan Raimanu; Serlia R Lamandasa (Jurnal Simki Economic, 2023)
This research departs from an empirical study that MSME actors must be able to utilize technology as a business strategy during the COVID-19 pandemic. Social media marketing is one of the strategies that can be taken by MSME actors in their efforts to increase business value and relationship quality with consumers. This study aims to test hypotheses based on causality between variables, namely social media marketing with online communities, interaction, sharing content, accessibility, and credibility variables on business value for MSMEs as social media users in running a business. The type of research used in this study is quantitative research with a total sample of 130 MSME respondents in the Poso Regency. The data collection technique in this study used an online survey which was distributed online through social media platforms. The data processing technique was carried out by statistical analysis of multiple linear regression using SPSS 25 software. The results showed that partially the Online Communities (X1), Sharing of Content (X3), Credibility (X5) variables affected the Business Value (Y) variable. And simultaneously, Variables Online Communities (X1), Interaction (X2), Sharing of Content (X3), Accessibility (X4), Credibility (X5) have a positive effect on Business Value (Y) with a coefficient of determination of 70% while the remaining 30% influenced by other variables not included in this study.